ANALISIS KEBUTUHAN PENDIDIKAN KESEHATAN REPRDUKSI DAN SEKSUALITAS PADA WANITA PUS MUDA DI KECAMATAN SUMOWONO TAHUN 2017 - Yana Ckristika Galingging; Djoko Nugroho; Farid Agusyahbana (Jurnal Kesehatan Masyarakat (Undip), 2018)
Sumowono is one sub district located in Semarang district with a number of young marriages in 2017 as many as 260 couples were married at a young age marriages as much as 25.38% in women. Teenagers who marry young more vulnerable to reproductive health and sexuality. Reproductive health and sexuality is often the case that k HIV (63 cases) and AIDS (19 cases), unwanted pregnancy (15%), abortion (20%), domestic violence (1%) and divorce (16%). The research objective to analyze the needs of reproductive health and sexuality education. The study was a descriptive cross sectional study design. The population is all women who married young age officially in District Sumowono in 2017 amounted to 66 people. The sampling technique using simple random sampling with a total of 39 people. Data were analyzed by univariate and bivariate descriptive. The results of the univariate study most of the age group 15-19 years (51.3%), lack of knowledge (59%), the attitude agreed (53.8%), less practice (82.1%) and the need for reproductive health and sexuality education (94.9%). The results of the bivariate deskripstif majority of respondents to the needs of the high reproductive health education in the age group of 20-24 years (89.5%), lack of knowledge (87%), the attitude agreed (84.2%) and practice less (81.2%). Suggested improve knowledge of reproductive health and sexuality to young married women by applying a form of media booklets that can drive the understanding of respondents and as a source of information and the handles are easy to carry and practical.